An Observational Study on Cognitive Function, Sleep Quality, Depression, Educational Background, and Functional Independence on Elderly at Sasana Tresna Werdha RIA Pembangunan Nursing Home, Ciracas, East Jakarta, Indonesia - Satyo, Yovian Timothy; Hawari, Irawaty (Universitas Malahayati, 2024)
ABSTRACT Along with the development of society and healthcare technology, there are an increase in life expectancy and the elderly population. They must be differentiated from simply older adults because they have their own set of health problems associated with the aging process now known as geriatric syndromes. Sleep disorder, cognitive function decline, and depression are common health problems that are often found in the elderly. They are interconnected and influenced by other factors such as educational background. The culmination of all of those factors is the decrease of the elder’s quality of life in the form of functional disability. To get a description of the cognitive function, sleep quality, depression, educational background, and functional independence of the elders at Sasana Tresna Werdha RIA Pembangunanan Nursing Home. The data obtained in this research are a significant predictor of the elders’ quality of life and can serve as a foundation for both analytical and interventional studies that aims to improve the elder’s quality of life. This research uses an observational descriptive approach using a cross-sectional method at Sasana Tresna Werdha RIA Pembangunan Nursing Home. The population for this research is all of the elderly that lives there and meets the inclusion criteria for this research which is still able to be interviewed. In total there are 44 elders that participated in this research. The sampling technique used in this research was total sampling. The data will be collected by interview using questionaires. The data will be analyzed using a univariate analysis in which categorical data will be presented its proportion in frequency and its percentage while numerical data will be presented with its mean and standard deviation if its distribution is parametrical and will be presented with its median and interquartile range if its distribution is non-parametrical. Furthermore, a crosstab will be made between two variables to be observed in more detail the possibilities of interrelationship bertween the two variables. The description of the elders’s cognitive function is that out of 44 elders, 30 (68.2%) are normal, 4 (9.1%) are categorized as mild cognitive impairment, and 10 (22.7%) are categorized as dementia. The description of the elders’ sleep quality is that 13 (29.5%) have good sleep quality and 31 (70.5%) have poor sleep quality. The description of the elder’s depression is that 29 (65.9%) are normal, 7 (15.9%) have mild depression, 4 (9.1%) have moderate depression, and 4 (9.1%) had severe depression. The description of the elders’ educational background is that 5 (11.4%) have low educational background, 10 (22.7%) have moderate educational background, 28 (63.6%) had high educational background, and 1 (2.3%) have unknown educational background. The description of the elder’s functional independence is that 10 (22.7%) are totally dependent, 2 (4.5%) are severely dependent, 7 (15.9%) are moderately dependent, 2 (4.5%) are mildly dependent, and 23 (52.3%) are independent. The majority of the elders at Sasana Tresna Werdha RIA Pembangunan have a normal cognitive function, have poor sleep quality, have no depression, have a high educational background, and are still functionally independent. Keywords: Cognitive Function, Sleep Quality, Depression, Educational Background, Functional Independence